2022
DOI: 10.1186/s40942-022-00418-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for epiretinal membrane formation and peeling following pars plana vitrectomy for primary rhegmatogenous retinal detachment, an OCT guided analysis

Abstract: Background To evaluate the rate and risk factors of epiretinal membrane (ERM) formation and need for ERM peeling after pars plana vitrectomy (PPV) for uncomplicated primary rhegmatogenous retinal detachment (RRD). Methods Retrospective, single-center, cohort study of 119 consecutive patients (119 eyes) that underwent RRD repair using PPV. The primary outcomes were ERM formation, classified using an optical coherence tomography grading system, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The study also identified several risk factors for ERM formation, including intraoperative cryotherapy, more than 1000 laser shots, 360° laser photocoagulation, and choroidal detachment [5]. The study found that visually significant ERM formation following PPV for primary RRD was uncommon in this cohort (5%) [5]. Our findings extend this understanding to the context of complex diabetic TRD, emphasizing the intricate relationship between retinal pathology, surgery, and subsequent ERM development.…”
Section: Exploring Factors Influencing Erm Development Following Vitr...supporting
confidence: 61%
See 1 more Smart Citation
“…The study also identified several risk factors for ERM formation, including intraoperative cryotherapy, more than 1000 laser shots, 360° laser photocoagulation, and choroidal detachment [5]. The study found that visually significant ERM formation following PPV for primary RRD was uncommon in this cohort (5%) [5]. Our findings extend this understanding to the context of complex diabetic TRD, emphasizing the intricate relationship between retinal pathology, surgery, and subsequent ERM development.…”
Section: Exploring Factors Influencing Erm Development Following Vitr...supporting
confidence: 61%
“…According to a retrospective, single-center, cohort study of 119 consecutive patients (119 eyes) that underwent PPV for uncomplicated primary RRD, postoperative ERM formation occurred in 69 eyes (58.0%) [5]. The study also identified several risk factors for ERM formation, including intraoperative cryotherapy, more than 1000 laser shots, 360° laser photocoagulation, and choroidal detachment [5]. The study found that visually significant ERM formation following PPV for primary RRD was uncommon in this cohort (5%) [5].…”
Section: Exploring Factors Influencing Erm Development Following Vitr...mentioning
confidence: 99%
“…A recent study indicated that half of the eyes treated by PPV for primary RRD had visible ERMs on optical coherence tomography. However, visual acuity was not impacted in the majority of these eyes, and only 5% of eyes required subsequent surgery for ERM removal 21 . Therefor, to evaluate short-term outcomes, our data evaluated the re-surgery rate and there was no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 93%
“…These factors are presumably responsible for the differences in incidence rates. Szigiato et al [13] reported that approximately half of the ERM formation following vitrectomy was detected after the first post-operative year. The long follow-up period of our study may have affected the results.…”
Section: Discussionmentioning
confidence: 99%